Beneficial effect of ustekinumab in familial pityriasis rubra pilaris with a new missense mutation in CARD14. (1st October 2017) - Lwin, S.M.; Hsu, C‐K.; Liu, L.; Huang, H‐Y.; Levell, N.J.; McGrath, J.A.
Summary: Pityriasis rubra pilaris (PRP) represents a group of rare chronic inflammatory skin disorders in which around one in 20 affected individuals show autosomal dominant inheritance. In such cases there may be gain‐of‐function mutations in CARD14, encoding caspase recruitment domain‐containing protein 14 (CARD14), which activates the noncanonical nuclear factor (NF)‐κB pathway, thereby promoting cutaneous inflammation. Here we report a mother and son with PRP due to a new missense mutation in CARD14 and describe the beneficial clinical effects of ustekinumab, a monoclonal antibody against interleukins 12 and 23, in both patients. A 49‐year‐old woman and her 20‐year‐old son had lifelong, generalized, patchy erythematous scale with a few islands of sparing, as well as minor nail ridging and mild palmoplantar keratoderma, features consistent with generalized PRP. Topical steroids, phototherapy and oral retinoids proved ineffective. Following informed consent, Sanger sequencing of CARD14 in both individuals revealed a new heterozygous single‐nucleotide transversion in exon 4, c.356T>G, resulting in the missense mutation p.Met119Arg. Ustekinumab, at a dose of 45 mg every 12 weeks, brought about a significant physical and emotional improvement in both the mother and son within a few days of the initial dose, which was sustained on maintenance dosing. This report highlights the therapeutic potential of biologics that downregulate NF‐κB signalling in familial PRP with mutations in CARD14 . Abstract : What's already known about this topic? Pityriasis rubra pilaris (PRP) represents a group of rare chronic inflammatory skin disorders in which some cases show autosomal dominant inheritance. Some cases also reveal heterozygous gain‐of‐function mutations in CARD14, encoding caspase recruitment domain‐containing protein 14 (CARD14). Ustekinumab, an interleukin‐12/23 antagonist, is a licensed biological therapy for psoriasis, although its use has not been widely assessed in PRP, despite anecdotal reports of its potential efficacy. What does this study add? We report a mother and son with refractory generalized PRP. DNA sequencing revealed that both carried a new de novo missense mutation in CARD14, p.Met119Arg. Identification of this CARD14 mutation was used as justification for a trial of ustekinumab, whereupon both patients had a beneficial clinical response, physically and emotionally, with sustained improvements over several months of follow‐up. Ustekinumab may be considered as a targeted anti‐inflammatory therapy for familial PRP with an underlying mutation in CARD14 .